Cyber Blockades: Towards a Theory of Informational Warfare in the Digitial Era. - Russell, Alison. (2017)
Abstract: International relations theories emphasize the importance of power in the world system and the role that technological innovation can play in reshaping power structures and modifying the importance of geography. In the Information Age, networks of power are defined as networks of communication. Cyberspace is the quintessential modern communication network; it is a critical part of the information revolution that has changed the way people and institutions interact and shaped the way we share ideas and information. The study of rules and norms for cooperation and conflict in cyberspace is still unfolding, and there is much work to be done to understand how this impacts modern society. Cyber warfare is a relatively new area of study, and there are many serious efforts under way to understand this new domain and the threats to it, particularly how older techniques of attack can be adapted to fit new technology. The driving issue for this research is how traditional warfare can help us understand cyber warfare. The two main research questions seek to define and explain blockades in cyberspace and understand the conditions under which they occur. The primary hypothesis is that cyber blockades are a modern form of blockade operations that are employed because they offer specific advantages with regards to vulnerabilities, goals, and alternative options.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Andrew Hess.; Committee: Robert Pfaltzgraff, and William Martel.; Keywords: International relations, Web studies, and Military studies.